DIVERSIFIKASI MANGGA OFF GRADE MENJADI SELAI DAN DODOL - Cahyuni Novia; Syaiful Syaiful; Deny Utomo (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2015)
Karanganyar village is a good mango producing area of excellent quality and off grade. The lack of knowledge about the processing of mango off grade diversification leads to lower selling prices. Training diversified manufacture of processed mango off grade into jams and dodol is appropriate for the conditions of rural communities Karanganyar. Manufacture of butter and mango dodol off grade is focused on the handling and processing of raw materials are accurate and correct, so that the resulting product quality. The method used is lectures and applications making of jam and mango dodol off grade and their packaging. Achievement on the training of making jam and mango dodol off grade is a partner all participants can make jam and dodol well and their packaging.